2013
DOI: 10.1021/jp401703p
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Atom in EGaIn/Ga2O3 Tunneling Junctions Comprising Self-Assembled Monolayers

Abstract: We compared the electrical properties of selfassembled monolayers (SAMs) formed on template-stripped Au from two homologous series of five different oligo-(phenylene)s bearing alkane thiol tails. The terminal phenyl ring is substituted by a 4-pyridyl ring in one series, thus the two differ only by the substitution of C−H for N. We formed tunneling junctions using the liquid metal eutectic Ga−In (EGaIn) as a nondamaging, conformal top contact that is insensitive to functional groups and measured the currentdens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 64 publications
12
93
1
3
Order By: Relevance
“…In air, log |J| drop − log |J| conical ≈ 1.8, while in a nitrogen environment, the difference is ∼2. 8. These values are in rough agreement with those reported by Simone et al, 1 where the conformal nature of a Hg drop caused an observed increase by a factor of ∼10 3 in J(V), relative to the contact area of a conical-tip junction.…”
Section: Chemistry Of Materialssupporting
confidence: 91%
“…In air, log |J| drop − log |J| conical ≈ 1.8, while in a nitrogen environment, the difference is ∼2. 8. These values are in rough agreement with those reported by Simone et al, 1 where the conformal nature of a Hg drop caused an observed increase by a factor of ∼10 3 in J(V), relative to the contact area of a conical-tip junction.…”
Section: Chemistry Of Materialssupporting
confidence: 91%
“…Previously, we have reported on the mechanism of charge transfer across molecular diodes with SAMs of SC 11 Fc on ultra-flat template-stripped silver-bottom electrodes (Ag TS ; henceforth left electrode) and EGaIn top electrodes (henceforth right electrode; a non-Newtonian liquid-metal alloy of eutectic In and Ga) [17][18][19] , including temperature-dependent J(V) measurements 20 (others have studied the mechanism rectification of SC n Fc SAMs in other types of junctions [21][22][23] ). This so-called 'EGaIn' technique is well established [24][25][26][27] and has been used in a wide range of physical-organic studies 20,[28][29][30][31][32][33] . The HOMO is located at the Fc unit, which is separated from the left electrode by the alkyl chain (similar to the junction schematically shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the Fermi energy of the contacts has to fall between the HOMO and LUMO of the molecule in the junction, for molecules conducting via a tunneling mechanism one expects the β value to depend upon the HOMO-LUMO separation, with more conjugated molecules having a smaller HOMO-LUMO gap and hence a smaller β. For instance, for a series of oligophenyl methanethiols (C 6 H 5 CH 2 SH, C 6 H 5 C 6 H 4 CH 2 SH, and C 6 H 5 C 6 H 4 C 6 H 4 CH 2 SH), β was determined as 4.6 ± 0.7 nm −1 using the GaIn/Ga 2 O 3 eutectic contact technique on self-assembled monolayers of the molecules on template-stripped gold electrodes [35] (a similar value, 4.2 ± 0.7 nm −1 , was determined earlier using a conducting AFM technique [36]), while for a series of oligothiophenes with 5, 8, 11, and 14 2,5-coupled thiophene rings, β was 1 nm −1 , measured by the STM break junction method [21]. The lowest β values so far measured have been for extended viologens (0.06 nm −1 ) [37] and for conjugated fused oligoporphyrins, oligoporphyrin-ethynylene, and oligoporphyrinbutadiynylene systems, where values of 0.2-0.4 nm −1 have been found, the exact value depending on structure [24][25][26][27].…”
Section: -3mentioning
confidence: 99%